PENGARUH MACROECONOMIC DAN ECONOMIC ACTIVITY ASEAN TERHADAP KINERJA IHSG INDONESIA (Studi pada Negara Singapura, Malaysia, Thailand, Filipina, dan Brunei Darussalam Tahun 2014—2016) - Harisatul Agustin; Suhadak Suhadak; Ari Darmawan (Jurnal Administrasi Bisnis, 2018)
The establishment of ASEAN Economic Community in 2013 integrates economic activity among ASEAN member countries in all aspects of the economy, such as free trade, goods movement, investment portfolio, foreign direct investment, etc. Implementation of the ASEAN Economic Community affects the economies of ASEAN countries in general. One of the significant impacts of ASEAN Economic Community for Indonesia is the significant movement of the Composite Stock Price Index (IHSG) at the end of 2014. This study aims to determine and analyze the macroeconomic and economic activity of ASEAN countries on the Performance of IHSG Indonesia ahead of the enactment of ASEAN Economic Community. The type of research is explanatory research with descriptive quantitative approach. The sample of research is five countries with the highest total economic activity to Indonesia. Data analysis technique is Partial Least Square (PLS) with PLS algorithm and PLS bootstrapping test. The evaluation is outer model, inner model, and goodness of fit. The results showed that macroeconomic effect on economic activity in the countries of Singapore, Malaysia, Brunei Darussalam and ASEAN. Macroeconomic Thailand and ASEAN influence the performance of IHSG Indonesia, and the economic activity of all sample countries does not affect the performance of IHSG Indonesia. Key words: Macroeconomic, Economic activity, Performance of IHSG Indonesia, t-statistic, ASEAN ABSTRAK Terbentuknya ASEAN Economic Community pada tahun 2013 mengintegerasikan economic activity antar negara anggota ASEAN dalam segala aspek perekonomian, seperti perdagangan bebas, perpindahan barang, portfolio investment, foreign direct investment, dan lain sebagainya. Implementasi ASEAN Economic Community memengaruhi perekonomian negara-negara di ASEAN secara umum. Salah satu pengaruh ASEAN Economic Community yang cukup signifikan bagi Indonesia adalah pergerakan Indeks Harga Saham Gabungan yang cukup signifikan pada akhir tahun 2014. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh macroeconomic dan economic activity negara-negara di ASEAN terhadap Kinerja IHSG Indonesia menjelang diberlakukannya ASEAN Economic Community. Jenis penelitian adalah explanatory research dengan pendekatan kuantitatif deskriptif. Sampel penelitian adalah lima negara dengan total economic activity tertinggi terhadap Indonesia. Teknik analisis data adalah Partial Least Square (PLS) dengan uji PLS algorithm dan PLS bootstrapping. Evaluasi yang dilakukan adalah outer model, inner model, dan goodness of fit. Hasil penelitian menunjukkan bahwa macroeconomic berpengaruh terhadap economic activity pada negara Singapura, Malaysia, Brunei Darussalam dan ASEAN. Macroeconomic Thailand dan ASEAN berpengaruh terhadap Kinerja IHSG Indonesia, dan economic activity seluruh negara sampel tidak berpengaruh terhadap Kinerja IHSG Indonesia. Kata Kunci: Macroeconomic, Economic Activity, Kinerja IHSG Indonesia, t-statistic, ASEAN